Leptin: New hope for the treatment of post-operative cognitive dysfunction? - Hua, Fei (International Scientific Literature, Inc., 2014)
Leptin plays a critical role in neuronal development and also promotes structural and functional activities in the central nervous system. Recent studies have demonstrated that leptin could produce therapeutic effects for cognitive impairments of patients with Alzheimer’s disease (AD). Post-operative cognitive dysfunction (POCD), defined as a significant dysfunction in cognitive performance for several weeks after surgery, probably has a pathogenesis similar to that of AD. Specifically, they are both characterized by cognitive impairment. In this regard, we hypothesized that leptin probably has a therapeutic benefit of alleviating symptoms of patients with POCD, and the leptin signaling pathway may be involved in the pathogenesis of POCD.